Quantitative Analysis of Impurities in Unfractionated Heparin of Bovine Origin - Workman, Wesley E.; Carrick, Kevin L. (Frontiers in Medicine, 2020)
The USP heparin sodium monograph lists impurities with specifications developed for porcine derived products. Most of these impurities are of biological origin and are present in porcine intestinal mucosa, the tissue source used in the production of porcine heparin. One of the specified impurities, oversulfated chondroitin sulfate (OSCS), has been introduced in the monograph to detect intended adulteration of heparin products with this impurity. The evaluation of bovine intestinal heparin as an alternative source of pharmaceutical heparin included an evaluation of bovine heparin with the current USP heparin sodium monograph methods. This evaluation included a comparison of impurity quantities observed in multiple bovine intestinal heparin samples against the specifications found in the USP heparin sodium monograph. The impurities investigated in this study were protein, galactosamine, nucleotidic impurities, and OSCS. Bovine intestinal heparin met the requirements in the tests for protein, galactosamine and nucleotidic impurities. A potential issue was observed with the strong anion exchange high performance liquid chromatography (SAX-HPLC) used to analyze for the presence of OSCS. While the OSCS was well resolved from the bovine heparin peak, the resolution of dermatan sulfate from heparin did not consistently meet system suitability requirements in the current USP Heparin sodium monograph. The overall levels of impurities observed in bovine intestinal mucosal heparin were comparable to those observed in porcine intestinal mucosal heparin. Bovine intestinal mucosal heparin can be produced with acceptable impurity levels that align with these important quality attributes found in porcine heparin.